Mesoporous SBA-15 modified with titanocene complexes and ionic liquids: interactions with DNA and other molecules of biological interest studied by solid state electrochemical techniques. Issue 37 (22nd August 2018) - del Hierro, Isabel; Gómez-Ruiz, Santiago; Pérez, Yolanda; Cruz, Paula; Prashar, Sanjiv; Fajardo, Mariano
Abstract : The effect of the functionalization of SBA-15 with titanocene derivatives and ionic liquids in biological processes has been tested by electrochemical techniques. Abstract : The immobilization of two titanocene complexes on SBA-15 has been accomplished following post-synthetic procedures. The ionic liquid, 1-methyl-3-[(triethoxysilyl)propyl]imidazolium chloride, has also been incorporated into the titanium containing materials to determine its influence on the interaction with molecules of biological interest. Cyclic voltammetry has been used to study the influence of the ionic liquid on the mechanism of reduction of titanocene derivatives. The interaction of titanocene and titanocene/ionic liquid-containing mesoporous silica SBA-15 materials, with molecules of biological interest associated with important processes of metallodrug action against cancer cells, has been studied. Thus, we have carried out hydrolysis experiments on the materials functionalized with titanocene derivatives in physiological media to determine their stability and the interaction with serum/transport proteins such as transferrin and BSA and with target molecules such as guanosine, single-stranded DNA and double-stranded DNA by means of solid state voltammetry techniques. A qualitative analysis of the data based on peak current and reduction potential value changes of the couple Ti(iv )/Ti(iii ) in the presence of biomolecules at physiological pH, has revealed that grafted titanocene complexes show higher affinity for serum/transport proteins than for nucleic acids, indicating that the transport steps to the cells may be easier than the subsequent attack on DNA.